SERIAL VERB CONSTRUCTION IN BAWEANESE: A TYPOLOGYCAL LINGUISTIC STUDY - Nur Amalina Sari; Agus Subiyanto (University of Muhammadiyah Malang, 2023)
The variety of languages in Indonesia is an attraction for research material in the field of language itself, one of research on serial verb construction in this study is the Bawean language or Baweanese for the object of study. This study aims to identify and describe the characteristics of serial verb construction (SVC) in Baweanese, and to analyze the semantic types of SVC in Bawean. The method used in this study is descriptive qualitative, which the data collection has used interview techniques with native speakers of the Baweanese, and also library methods to find references to previous studies to compare in this research. The result can be shown in the pattern of forming SVC of Baweanese are (1) transitive V1 + transitive V2, (2) intransitive V1 + transitive V2, (3) transitive V1 + intransitive V2, and (4) intransitive V1 + intransitive V2. Then, the types of verb serialization (VS) that can be identified include: (1) manner, (2) locative, (3) directional, (4) purpose, (5) movement, (6) instrumental, (7) cause-effect. The conclusion obtained is that BBW has similarities in the pattern of formation of SVC of Madura language, but in terms of written language and dialect it is not similar.